Composite solid electrolyte membrane, preparation method thereof and solid-state battery

The second solid electrolyte is filled with pores of the first solid electrolyte layer by hot pressing treatment, which solves the problem of low density of the solid electrolyte membrane and improves lithium ion transmission capability and battery safety.

CN119315095APending Publication Date: 2025-01-14SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411476468.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing solid electrolyte membrane has low density, which leads to interface problems and growth of lithium dendrites, causing battery short circuits, and poses safety hazards.

Method used

Using the hot pressing method, the first solid electrolyte layer and the second solid electrolyte are processed, so that the second solid electrolyte is converted from solid state to liquid state, fill the pores of the first solid electrolyte layer, and form a composite solid electrolyte membrane with low porosity. .

Benefits of technology

The density and lithium ion transmission capacity of the composite solid electrolyte membrane are improved, the interface resistance is reduced, the growth of lithium dendrites is suppressed, and the safety and cycle life of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315095A_ABST
    Figure CN119315095A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte membrane, a preparation method thereof and a solid-state battery, and relates to the technical field of energy storage. The preparation method comprises the following steps: preparing a first solid electrolyte layer, wherein the first solid electrolyte layer comprises a first solid electrolyte; carrying out hot pressing treatment on the first solid electrolyte layer and the second solid electrolyte layer, and cooling to obtain a composite solid electrolyte membrane; in the hot pressing treatment, the second solid electrolyte is converted into a liquid state from a solid state. By adopting the preparation method, the density of the composite solid electrolyte membrane can be improved, the interface problem is solved, the interface resistance is reduced, the growth of lithium dendrites is inhibited, and the ionic conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery. Background Art

[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid state electrolytes (SSE) instead of flammable organic liquid electrolytes or gel electrolytes for ion transport, and have higher safety, higher energy density, faster charging speed and longer cycle life.

[0003] The current method for preparing solid electrolyte membranes includes directly pressing a single solid electrolyte particle into a solid electrolyte membrane, or pressing a single solid electrolyte particle into a solid electrolyte membrane after mixing it with a binder such as polytetrafluoroethylene (PTFE). However, due to the defects or gaps between the solid electrolyte particles, the solid electrolyte membrane prepared by the above method has a low density, is prone to interface problems, and causes lithium dendrites to grow through the gaps, which may cause battery short circuits and safety hazards. Summary of the invention

[0004] Based on this, it is necessary to provide a composite solid electrolyte membrane and a preparation method thereof, and a solid-state battery to improve the density of the solid electrolyte membrane.

[0005] In a first aspect, the present application provides a method for preparing a composite solid electrolyte membrane, the method for preparing the composite solid electrolyte membrane comprising:

[0006] preparing a first solid electrolyte layer, wherein the first solid electrolyte layer comprises a first solid electrolyte;

[0007] The first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing treatment, and then cooled to obtain a composite solid electrolyte membrane;

[0008] During the hot pressing process, the second solid electrolyte is transformed from a solid state to a liquid state.

[0009] In some embodiments, the temperature T0 of the hot pressing treatment, the melting point T1 of the first solid electrolyte, and the melting point T2 of the second solid electrolyte satisfy:

[0010] T0<T1;

[0011] T0-T2=(0~50)℃;

[0012] Preferably, the melting point of the second solid electrolyte is in the range of 80°C to 200°C.

[0013] In some of the embodiments, before the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing, the process further includes: laying a granular second solid electrolyte on the surface of the first solid electrolyte layer.

[0014] In some embodiments, m1g of the second solid electrolyte particles are laid on the surface of the first solid electrolyte layer, the first solid electrolyte layer contains m0g of the first solid electrolyte, and m1 / m0=1:(3~50).

[0015] In some embodiments, a granular second solid electrolyte is laid on the surface of the first solid electrolyte layer to form a solid electrolyte membrane precursor, and a sponge roller is used to roll the solid electrolyte membrane precursor.

[0016] In some embodiments, the particle size D50 of the second solid electrolyte is 0.1 μm to 1 μm.

[0017] In some embodiments, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal element or a combination of metal elements with an average valence of trivalent, and x satisfies 0<x<6;

[0018] Preferably, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ 、Bi 3+ , one or more of +3 valent lanthanide metals;

[0019] Preferably, 2≤x≤5.

[0020] In some embodiments, the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing to obtain a composite solid electrolyte membrane, comprising:

[0021] After forming a second solid electrolyte on one side surface of the first solid electrolyte layer, a first hot pressing treatment and cooling are performed to form a first intermediate;

[0022] After forming the second solid electrolyte on the surface of the first intermediate that does not contain the second solid electrolyte, the composite solid electrolyte membrane is formed by a second hot pressing treatment and cooling.

[0023] In some embodiments, the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing to obtain a composite solid electrolyte membrane, comprising:

[0024] A second solid electrolyte is formed on the first solid electrolyte layer to obtain an intermediate, and the intermediate is subjected to heat pressing treatment to obtain a composite solid electrolyte membrane after cooling.

[0025] In some embodiments, the hot pressing treatment satisfies at least one of the following conditions (1) to (3):

[0026] (1) The hot pressing temperature of the hot pressing treatment is 80°C to 200°C;

[0027] (2) The hot pressing time of the hot pressing treatment is 0.5min~30min;

[0028] (3) The hot pressing pressure of the hot pressing treatment is 60MPa~600MPa.

[0029] In some embodiments, the first solid electrolyte layer has a thickness of 50 μm.

[0030] In a second aspect, the present application further provides a composite solid electrolyte membrane, which is a composite solid electrolyte membrane prepared by the preparation method provided in the first aspect of the present application.

[0031] In a third aspect, the present application also provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane provided in the second aspect of the present application located between the positive electrode sheet and the negative electrode sheet, or a composite solid electrolyte membrane prepared by the preparation method provided in the first aspect of the present application.

[0032] The above-mentioned composite solid electrolyte membrane preparation method, by preparing the first solid electrolyte layer, the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing treatment, during the hot pressing treatment, the second solid electrolyte is transformed from solid to liquid, so that the second solid electrolyte and the first solid electrolyte layer are more closely combined, and the second solid electrolyte can flow into the pores of the first solid electrolyte under a certain pressure after melting, thereby helping to fill the pores of the first solid electrolyte layer, and after cooling and solidification, a composite solid electrolyte membrane with low porosity is prepared. In this application, by preparing the first solid electrolyte layer and combining the phase change of the second solid electrolyte, the combination between the first solid electrolyte and the second solid electrolyte in the composite solid electrolyte membrane is made closer, which is conducive to reducing the porosity and roughness of the composite solid electrolyte membrane, improving the density of the composite solid electrolyte membrane, improving interface problems, reducing interface resistance, and inhibiting the growth of lithium dendrites. At the same time, since the first solid electrolyte and the second solid electrolyte both have lithium ion transmission capabilities, the lithium ion transmission capability of the composite solid electrolyte membrane can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] FIG. 1 is a flow chart of a method for preparing a composite solid electrolyte membrane in one embodiment of the present application. DETAILED DESCRIPTION

[0034] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0035] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0036] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0037] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0038] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, it is mentioned that the method may also include step S16, which means that step S16 may be added to the method in any order, for example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.

[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] The current solid electrolyte membrane is limited by the defects of solid electrolyte particles or the gaps between particles, and has a low density. The lithium deposition / stripping caused by the uneven electric field and ion distribution at the interface can easily cause a huge volume change of the lithium metal electrode material. Local excessive lithium deposition / stripping will lead to the continuous renewal of the electrolyte membrane and electrode interface, resulting in the continuous occurrence of interfacial reactions and the continuous increase of interfacial impedance. In addition, due to the uneven deposition of lithium ions on the electrode surface, lithium dendrites are easily grown, which usually occurs on lithium metal negative electrodes. The low density of the solid electrolyte membrane causes lithium dendrites to grow through the gaps, so that the lithium metal negative electrode penetrates into the electrolyte during the lithium metal battery cycle, which may cause battery short circuits and safety hazards.

[0044] When preparing solid electrolyte membranes, traditional technology can improve interface performance by reducing the particle size of solid electrolyte particles. However, the reduction in the particle size of solid electrolyte particles will lead to a decrease in the ionic conductivity of the solid electrolyte membrane, and its improvement on density is not obvious.

[0045] As shown in FIG. 1 , a first aspect of an embodiment of the present application provides a method for preparing a composite solid electrolyte membrane, the method comprising the following steps:

[0046] S1. Prepare a first solid electrolyte layer.

[0047] The first solid electrolyte layer includes a first solid electrolyte.

[0048] The embodiment of the present application does not specifically limit the type of the first solid electrolyte. Any known solid electrolyte can be used in the present application without violating the inventive concept of the present application. As an illustrative example only, not a limitation on the scope of protection, the first solid electrolyte includes but is not limited to one or more of an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.

[0049] The present application embodiment does not specifically limit the preparation steps of the first solid electrolyte layer. Any known preparation steps of the solid electrolyte layer can be used in the present application without violating the inventive concept of the present application. As an illustrative example only, not a limitation on the scope of protection, the first solid electrolyte layer can be formed by a dry molding process or a wet molding process.

[0050] It can be understood that the step of using a dry molding process may include, in the absence of a solvent, placing the first solid electrolyte material into a mold for tableting, or placing the mixture after mixing the first solid electrolyte material and the binder into a mold for tableting, to obtain a first solid electrolyte layer including the first solid electrolyte. The step of using a wet molding process may include dispersing the first solid electrolyte in a solvent to form a slurry, or dispersing the first solid electrolyte and the binder in a solvent to form a slurry, applying the slurry to the surface of the substrate and drying it, to obtain a first solid electrolyte layer including the first solid electrolyte.

[0051] S2, hot pressing the first solid electrolyte layer and the second solid electrolyte, and cooling to obtain a composite solid electrolyte membrane.

[0052] The second solid electrolyte is transformed from a solid state to a liquid state during the hot pressing process.

[0053] The second solid electrolyte of the embodiment of the present application undergoes a phase change during the hot pressing process, from a solid state to a liquid state with fluidity. The liquid second solid electrolyte can diffuse along the interface between the first solid electrolyte layer and the second solid electrolyte, filling the microscopic unevenness or gaps that may have existed, and increasing the contact area between the second solid electrolyte and the first solid electrolyte layer. The larger interface contact area can improve the bonding quality of the interface, thereby enhancing the density of the overall structure.

[0054] The above-mentioned composite solid electrolyte membrane preparation method, by preparing the first solid electrolyte layer, the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing treatment, during the hot pressing treatment, the second solid electrolyte is transformed from solid to liquid, so that the second solid electrolyte and the first solid electrolyte layer are more closely combined, and the second solid electrolyte can flow into the pores of the first solid electrolyte under a certain pressure after melting, thereby helping to fill the pores of the first solid electrolyte layer, and after cooling and solidification, a composite solid electrolyte membrane with low porosity is prepared. In this application, by preparing the first solid electrolyte layer and combining the phase change of the second solid electrolyte, the combination between the first solid electrolyte and the second solid electrolyte in the composite solid electrolyte membrane is made closer, which is conducive to reducing the porosity and roughness of the composite solid electrolyte membrane, improving the density of the composite solid electrolyte membrane, improving interface problems, reducing interface resistance, and inhibiting the growth of lithium dendrites. At the same time, since the first solid electrolyte and the second solid electrolyte both have lithium ion transmission capabilities, the lithium ion transmission capability of the composite solid electrolyte membrane can be effectively improved.

[0055] In some embodiments, the temperature T0 of the hot pressing treatment, the melting point T1 of the first solid electrolyte, and the melting point T2 of the second solid electrolyte satisfy the following relationship: T0<T1; T0-T2=(0-50)°C.

[0056] In the embodiment of the present application, the temperature of the hot pressing treatment is lower than the melting point of the first solid electrolyte, so that during the composite process of the first solid electrolyte and the second solid electrolyte, the first solid electrolyte can remain solid and will not melt, so that the first solid electrolyte layer can maintain its inherent structure and performance, ensuring a certain mechanical strength and pore structure. The second solid electrolyte in liquid form can effectively penetrate into the microstructure of the solid first solid electrolyte layer, enhancing the bonding between the two, thereby improving the overall performance of the composite solid electrolyte membrane.

[0057] In the embodiment of the present application, by controlling the difference between the hot pressing temperature T0 and the melting point T2 of the second solid electrolyte within the range of (0~50)°C, on the one hand, during the hot pressing process, the second solid electrolyte can undergo a solid-to-liquid phase change under a certain pressure and flow into the pores of the first solid electrolyte layer; on the other hand, it can prevent excessively high hot pressing temperatures from damaging the structural properties of the second solid electrolyte or inducing unnecessary side reactions.

[0058] Preferably, the melting point of the second solid electrolyte is in the range of 80° C. to 200° C. The melting point of the second solid electrolyte includes but is not limited to 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C. or other values ​​satisfying the above range.

[0059] In some embodiments, during the hot pressing process of the first solid electrolyte layer and the second solid electrolyte, the temperature of the hot pressing process is 60°C to 250°C, including but not limited to 60°C, 70°C, 80°C, 100°C, 120°C, 140°C, 150°C, 160°C, 180°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or other values ​​satisfying the above range. In this way, the second solid electrolyte can be ensured to be transformed from a solid state to a liquid state during the hot pressing process and have a certain fluidity.

[0060] In some embodiments, during the hot pressing process of the first solid electrolyte layer and the second solid electrolyte, the hot pressing time is 0.5min~30min, including but not limited to 0.5min, 1min, 2min, 3min, 4min, 5min, 6min, 8min, 10min, 12min, 14min, 15min, 16min, 18min, 20min, 25min, 30min or other values ​​satisfying the above range. In this way, the second solid electrolyte can flow within a certain period of time and has a suitable flow range. When it can flow to the pores of the first solid electrolyte layer, it will not cause excessive loss of the second solid electrolyte, thereby ensuring the conductivity of lithium ions.

[0061] In some embodiments, during the hot pressing process of the first solid electrolyte layer and the second solid electrolyte, the pressure of the hot pressing process is 60MPa~600MPa, including but not limited to 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa, 350MPa, 400MPa, 450MPa, 500MPa, 550MPa, 600MPa or other values ​​satisfying the above range. In this way, the hot pressing pressure can promote the flow of the second solid electrolyte within a suitable range without destroying the structure of the first solid electrolyte layer.

[0062] In some embodiments, before the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing, the process further includes laying a granular second solid electrolyte on the surface of the first solid electrolyte layer.

[0063] The second solid electrolyte of the embodiment of the present application may be a granular dispersed phase rather than a continuous phase before hot pressing treatment. By laying the granular second solid electrolyte on the surface of the first solid electrolyte layer, the second solid electrolyte can be more evenly distributed on the surface of the first solid electrolyte layer. During hot pressing treatment, the granular second solid electrolyte undergoes a phase change, that is, it changes from a granular dispersed phase to a liquid phase with fluidity, and can flow into and fill the pores of the first solid electrolyte layer more evenly, thereby reducing the local heterogeneity and porosity of the prepared composite solid electrolyte membrane.

[0064] In some embodiments, m1g of the second solid electrolyte particles are laid on the surface of the first solid electrolyte layer, and the first solid electrolyte layer contains m0g of the first solid electrolyte, and m1 / m0=1:(3~50).

[0065] As an example, m1 / m0 can be 1:3, 1:5, 1:7, 1:9, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50 or other values ​​satisfying the above range. In this way, the appropriate content of the first solid electrolyte ensures that the second solid electrolyte can smoothly fill the gaps of the first solid electrolyte during the hot pressing process, thereby improving the conductivity of the overall composite solid electrolyte membrane. At the same time, an appropriate amount of the second solid electrolyte ensures that it has good fluidity during the hot pressing process without excessive loss, thereby maintaining the structural stability of the prepared composite solid electrolyte membrane and the reliability of the battery.

[0066] In some embodiments, a granular second solid electrolyte is laid on the surface of the first solid electrolyte layer to form a solid electrolyte membrane precursor, and a sponge roller is used to roll the solid electrolyte membrane precursor. In this way, by rolling with a sponge roller, the second solid electrolyte is more evenly laid on the surface of the first solid electrolyte layer, thereby facilitating the formation of a tighter interface during hot pressing. In addition, by rolling with a sponge roller, the granular second solid electrolyte can also be pre-filled into the first solid electrolyte layer, so that part of the second solid electrolyte powder enters the first solid electrolyte layer.

[0067] In some embodiments, the particle size D50 of the second solid electrolyte is 0.1~1μm, including but not limited to 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm or other values ​​satisfying the above range. In this way, the particle size of the second solid electrolyte is within a suitable range, and the second solid electrolyte can smoothly flow into the smaller pores of the second solid electrolyte layer and have a higher pore filling capacity to form a denser composite solid electrolyte membrane. At the same time, a more uniform conductive network is formed, reducing the resistance of ion conduction in the membrane, and effectively improving the overall lithium ion conductivity of the composite solid electrolyte membrane.

[0068] In some embodiments, the second solid electrolyte comprises Li3MCl 6-x Br x , M is a trivalent metal element or a combination of metal elements with an average valence of trivalent, and x satisfies 0<x<6.

[0069] It should be noted that, taking M as an example including two metal elements, assuming they are element A and element B, the second solid electrolyte can be Li3A y B z Cl 6-x Br x , the valence of element A is a, the valence of element B is b, and the combination of metal elements with an average valence of trivalent satisfies ay+bz=3.

[0070] The second solid electrolyte of the embodiment of the present application includes a solid electrolyte obtained by doping and modifying a Li3MCl6-based halide solid electrolyte with a halogen element Br. By replacing some of the chloride ions in the electrolyte with bromide ions with lower electronegativity and larger ionic radius, the strength of the ionic bond can be weakened, the melting point of the electrolyte material can be reduced, and the second solid electrolyte can be partially or completely melted at a lower temperature (80°C~200°C). After the second solid electrolyte is melted, it can flow into the pores of the first solid electrolyte under a certain pressure, thereby helping to fill the pores of the first solid electrolyte, reduce the porosity and roughness of the composite solid electrolyte membrane, improve the density of the composite solid electrolyte membrane, improve interface problems, reduce interface resistance, and inhibit lithium dendrite growth, and improve ionic conductivity.

[0071] Furthermore, bromide ions with a larger ionic radius replace some chloride ions in the electrolyte, increase the voids in the lattice or reduce the rigidity of the lattice, reduce the constraints on lithium ions, thereby facilitating the migration of lithium ions and improving the ionic conductivity of the composite solid electrolyte membrane. Bromide ions also have lower electronegativity, which helps reduce side reactions between the electrolyte and the electrode material, thereby improving the stability of the interface and extending the cycle life of the battery.

[0072] In some embodiments, M in the second solid electrolyte is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ 、Bi 3+ , one or more of +3 valent lanthanide metals. As an example, the second solid electrolyte includes but is not limited to Li3YCl3Br3, Li3YCl4Br2, Li3YCl5Br1, Li3YCl2Br4, Li3YCl1Br5, Li3In 0.5 Fe 0.5 Cl3Br3、Li3In 0.5 Fe 0.5 Cl4Br2、Li3In 0.5 Fe 0.5 Cl5Br1、Li3In 0.5 Fe 0.5 Cl2Br4、Li3In 0.5 Fe 0.5 One or more of Cl1Br5. Preferably, 2≤x≤5. More preferably, x=3, and the second solid electrolyte comprises Li3YCl3Br3.

[0073] In some embodiments, the first solid electrolyte may include a halide solid electrolyte material, and a halide solid electrolyte material with high flexibility and excellent deformation ability may be preferably selected. As an example, the first solid electrolyte includes Li2ZrCl6, Li7La3Zr2O 12 Thus, during the hot pressing process, the first solid electrolyte layer can achieve better and tighter fit with the second solid electrolyte, further improving the density of the composite solid electrolyte layer.

[0074] In some embodiments, the step of subjecting the first solid electrolyte layer and the second solid electrolyte layer to hot pressing may include one-step hot pressing and multi-step hot pressing.

[0075] In some optional embodiments, the one-step hot pressing process includes laying the second solid electrolyte on one side surface of the first solid electrolyte layer, applying a pressing force to the one side surface of the first solid electrolyte layer sprayed with the second solid electrolyte, performing hot pressing treatment, and cooling to obtain a composite solid electrolyte membrane.

[0076] As an example, after the granular second solid electrolyte is sprinkled onto one side surface of the first solid electrolyte layer at one time, the surface is subjected to heat pressing treatment, and the composite solid electrolyte membrane is formed after cooling.

[0077] In some optional embodiments, the step-by-step hot pressing process includes forming a second solid electrolyte on one side surface of the first solid electrolyte layer, performing a first hot pressing treatment and cooling to form a first intermediate; and forming a second solid electrolyte on one side surface of the first intermediate that does not contain the second solid electrolyte, performing a second hot pressing treatment and cooling to form a composite solid electrolyte membrane.

[0078] As an example, according to a preset mass ratio, a first solid electrolyte is used to prepare a first solid electrolyte layer with a corresponding mass of the first solid electrolyte. After a portion of the second solid electrolyte is sprinkled on one surface of the first solid electrolyte layer, it is subjected to a first hot pressing and cooling to form a first intermediate. The first intermediate is then turned over, and the other surface, i.e., the surface of the first intermediate that does not contain the second solid electrolyte, is sprinkled with the remaining second solid electrolyte. After a second hot pressing and cooling, a composite solid electrolyte membrane is formed.

[0079] In some optional embodiments, the second solid electrolyte is laid on the surface of the first solid electrolyte layer, or the second solid electrolyte is formed on the surface of the first solid electrolyte layer, and powdering can be carried out by a powder spraying mechanism, for example, the second solid electrolyte is sprayed onto the surface of the first solid electrolyte layer by a powder spraying mechanism.

[0080] The second aspect of the embodiment of the present application further provides a composite solid electrolyte membrane, which is prepared by the preparation method provided by the first aspect of the embodiment of the present application.

[0081] The third aspect of the embodiment of the present application further provides a solid-state battery, including a positive electrode sheet, a negative electrode sheet, and a composite solid electrolyte membrane located between the positive electrode sheet and the negative electrode sheet. The relevant contents of the composite solid electrolyte membrane can be referred to the above introduction, and will not be repeated here.

[0082] In the embodiment of the present application, the positive electrode plate includes a positive electrode collector and a positive electrode active electrode material layer formed on the current collector, and the negative electrode plate includes a negative electrode collector and a negative electrode active electrode material layer formed on the negative electrode collector.

[0083] The positive electrode active material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive material. The positive electrode active material is a compound that enables lithium to be reversibly embedded and de-embedded, specifically, it may include a layered oxide positive electrode, a spinel positive electrode, an olivine-type positive electrode and a polyanion positive electrode, sulfur and its compounds. Preferably, the mass proportion of the positive electrode active material contained in the positive electrode active material layer can be 80wt%-99wt%, such as 80wt%, 82wt%, 85wt%, 87wt%, 90wt%, 92wt%, 95wt%, 97wt%, 99wt%, etc., preferably 92wt%-98.5wt%.

[0084] The positive electrode binder is used to bind the components such as the positive electrode active material, the positive electrode conductive material and the positive electrode current collector together. Specifically, the positive electrode binder may include at least one selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber, preferably polyvinylidene fluoride. The mass proportion of the positive electrode binder contained in the positive active electrode material layer may be 1wt%-20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt%-10wt%.

[0085] The positive electrode conductive material is mainly used to assist and improve the conductivity in the secondary battery, and there is no particular limitation on it in the embodiments of the present application, as long as it has conductivity without causing chemical changes. Specifically, the positive electrode conductive material may include graphite, and the mass proportion of the positive electrode conductive material contained in the positive active electrode material layer may be 1wt%-20wt%, such as 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, etc., preferably 1.2wt%-10wt%.

[0086] There is no particular limitation on the negative electrode active material in the embodiments of the present application, as long as it is a material that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, and magnesium ions, such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These materials can be used alone, or two or more of them can be used in combination.

[0087] In order to explain the technical content, structural features, achieved objectives and effects of the technical solutions of the embodiments of the present application in detail, the following is a detailed description in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0088] Example 1

[0089] This embodiment provides a method for preparing a composite solid electrolyte membrane, comprising:

[0090] Step 101, preparing a first solid electrolyte layer: mixing the first solid electrolyte Li2ZrCl6 and the binder in a mass ratio of 99:1, and pressing at a pressure of 20 MPa to form a first solid electrolyte layer.

[0091] Among them, the melting point of the first solid electrolyte Li2ZrCl6 is 350°C, the thickness of the first solid electrolyte layer is 50 μm, and the ion conductivity of the first solid electrolyte layer is 0.83 mS / cm.

[0092] Step 102, laying a granular second solid electrolyte Li3YCl3Br3 on one side surface of the first solid electrolyte layer; the mass ratio of the second solid electrolyte to the first solid electrolyte is 1:8, and the particle size D50 of the second solid electrolyte particles is 0.3μm; the ionic conductivity of the second solid electrolyte Li3YCl3Br3 is 2.34mS / cm; the melting point of the second solid electrolyte Li3YCl3Br3 is 115°C.

[0093] Step 103, hot pressing treatment: applying a pressing force to the surface of the first solid electrolyte layer sprayed with the second solid electrolyte particle powder, performing hot pressing treatment, and cooling to obtain a composite solid electrolyte membrane. The pressing temperature of the hot pressing treatment is 130°C; the pressing time is 10 minutes; and the pressing pressure is 300 MPa.

[0094] The thickness of the composite solid electrolyte membrane prepared in this embodiment is 52 μm; the ion conductivity of the composite solid electrolyte membrane is 2.89 mS / cm; and the porosity of the composite solid electrolyte membrane is 5.0%.

[0095] In a second aspect, this embodiment further provides a method for preparing a solid-state battery, comprising the following steps:

[0096] (1) Preparation of positive electrode: NCM811, PTFE, super-P and Li2ZrCl6 were mixed uniformly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, fiberized to form a first mixture, and the first mixture was roll-pressed to form a first positive electrode layer; the rolling temperature was 60°C and the rolling time was 5 minutes; the positive electrode current collector and the first positive electrode layer were stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature was 150°C, the hot-pressing time was 10 minutes, and the hot-pressing pressure was 120 MPa.

[0097] (2) Preparation of negative electrode: Mix the negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 in a mass ratio of 69:4:2:25, put them into a high shear force equipment mixer, and perform fiberization to form a second mixture. The second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa;

[0098] (3) Assembling the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared in the first aspect to form a solid-state battery.

[0099] Example 2

[0100] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0101] In step 102, the mass ratio of the second solid electrolyte to the first solid electrolyte is 1:3.

[0102] Example 3

[0103] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0104] In step 102, the mass ratio of the second solid electrolyte to the first solid electrolyte is 1:50.

[0105] Example 4

[0106] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0107] In step 103, the pressing temperature of the hot pressing treatment is 95° C., the pressing time is 30 min, and the pressing pressure is 600 MPa.

[0108] Example 5

[0109] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0110] In step 103, the pressing temperature of the hot pressing treatment is 165° C., the pressing time is 0.5 min, and the pressing pressure is 60 MPa.

[0111] Example 6

[0112] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0113] In step 102, after laying the granular second solid electrolyte Li3YCl3Br3 on one side surface of the first solid electrolyte layer, it also includes using a sponge roller to roll the first solid electrolyte layer to lay the second solid electrolyte on one side surface, so that the second solid electrolyte at least partially enters the gap in the first solid electrolyte layer.

[0114] Example 7

[0115] This embodiment provides a method for preparing a composite solid electrolyte membrane, comprising:

[0116] Step 701, preparing a first solid electrolyte layer: the first solid electrolyte Li2ZrCl6 and the binder are evenly mixed in a mass ratio of 99:1, and pressed at a pressure of 20 MPa to form a first solid electrolyte layer.

[0117] Among them, the melting point of the first solid electrolyte Li2ZrCl6 is 350°C; the thickness of the first solid electrolyte layer is 50 μm; and the ion conductivity of the first solid electrolyte layer is 0.83 mS / cm.

[0118] Step 702, laying the granular second solid electrolyte Li3YCl3Br3 on the surface of one side of the first solid electrolyte layer; wherein the mass ratio of the second solid electrolyte laid this time to the first solid electrolyte is 3:40, and the particle size D50 of the second solid electrolyte particles is 0.3μm; the ionic conductivity of the second solid electrolyte Li3YCl3Br3 is 2.34mS / cm; the melting point of the second solid electrolyte Li3YCl3Br3 is 115°C.

[0119] Step 703, primary hot pressing treatment: applying a pressing force to the surface of the first solid electrolyte layer sprayed with solid electrolyte particle powder, hot pressing treatment, and cooling to obtain a first intermediate. The pressing temperature of the primary hot pressing treatment is 130°C; the pressing time is 10 min; and the pressing pressure is 300 MPa.

[0120] Step 704, secondary hot pressing treatment: after laying the second solid electrolyte on the surface of the first intermediate that does not contain the second solid electrolyte, a second hot pressing treatment and cooling are performed to form the composite solid electrolyte membrane. The mass ratio of the second solid electrolyte laid this time to the first solid electrolyte is 1:20, the pressing temperature of the secondary hot pressing treatment is 130°C; the pressing time is 10 min; and the pressing pressure is 300MPa.

[0121] Among them, the thickness of the composite solid electrolyte membrane prepared in this embodiment is 51.5 μm; the ion conductivity of the composite solid electrolyte membrane is 3.03 mS / cm; and the porosity of the composite solid electrolyte membrane is 4.1%.

[0122] Example 8

[0123] The preparation method of the solid electrolyte membrane and the preparation method of the solid-state battery in this embodiment are basically the same as those in Embodiment 1, except that:

[0124] The first solid electrolyte is an oxide solid electrolyte Li7La3Zr2O 12 , Li7La3Zr2O 12 The melting point is 750°C; the ionic conductivity of the first solid electrolyte layer is 0.46 mS / cm.

[0125] The second solid electrolyte is Li3In 0.5 Fe 0.5 Cl3Br3, the second solid electrolyte Li3In 0.5 Fe 0.5 The melting point of Cl3Br3 is 125℃, and the second solid electrolyte Li3In 0.5 Fe 0.5 The ionic conductivity of Cl3Br3 is 2.48mS / cm.

[0126] Comparative Example 1

[0127] The difference between Comparative Example 1 and Example 1 is that only the first solid electrolyte layer is prepared.

[0128] Comparative Example 2

[0129] The difference between Comparative Example 2 and Example 8 is that only the first solid electrolyte layer is prepared.

[0130] Comparative Example 3

[0131] The difference between Comparative Example 3 and Example 1 is that the second solid electrolyte is Li3InCl6, the ionic conductivity of the second solid electrolyte Li3InCl6 is 1.54 mS / cm, and the melting point of the second solid electrolyte Li3InCl6 is 490°C.

[0132] Comparative Example 4

[0133] The difference between Comparative Example 4 and Example 1 is that: no hot pressing treatment and cooling step are performed. Specifically, in step 103, a pressing force is applied to the surface of one side of the first solid electrolyte layer sprayed with the second solid electrolyte particle powder, and a pressing treatment is performed to obtain a composite solid electrolyte membrane. The pressing temperature of the pressing treatment is 45° C.; the pressing time is 10 min; and the pressing pressure is 300 MPa.

[0134] The relevant raw materials and process parameters in the preparation methods of Examples 1 to 8 and Comparative Examples 1 to 4 are listed in Table 1 below, where “-” means untreated.

[0135] Table 1

[0136]

[0137] The composite solid electrolyte membranes and corresponding solid-state batteries of the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to performance tests, and the test results are shown in Table 2 below, wherein the test conditions or test standards for each performance test item are as follows:

[0138] (1) Porosity test

[0139] The porosity of the first solid electrolyte layer and the porosity of the composite solid electrolyte membrane in the embodiment and the comparative example were detected using an SSA-4200 pore size and specific surface area analyzer.

[0140] (2) Thickness test

[0141] According to GB / T 6672-2001 standard, a Millimar film thickness gauge (Millimar C1208, Millimar, Germany) was used to measure the thickness of the composite solid electrolyte membrane in the examples and comparative examples.

[0142] (3) Electrolyte membrane conductivity test

[0143] At 25°C, the test structure of stainless steel sheet / solid electrolyte membrane / stainless steel sheet was used, the frequency range was 0.1Hz-7MHz, and the AC signal amplitude Z was 10 -2 The AC impedance test was carried out under the condition of V, and the ionic conductivity was calculated according to the formula σ=L / (S*R), where L is the thickness of the solid electrolyte membrane, S is the cross-sectional area of ​​the solid electrolyte membrane, and R represents the charge transfer resistance.

[0144] (4) Cyclic performance test

[0145] The solid-state lithium metal batteries in the embodiments and comparative examples were subjected to a cycle test. At a temperature of 25°C±2°C, in the first step, they were charged at 0.1C to a final voltage of 4.5V, a cutoff current of 0.05C, and allowed to stand for 30 minutes; in the second step, they were discharged at 0.1C to a final discharge voltage of 2.7V, the discharge capacity was recorded, and the battery was allowed to stand for 30 minutes; the first and second steps were repeated to test the cycle performance of the battery for 500 cycles.

[0146] Table 2

[0147]

[0148] Combining Table 1 and Table 2, it can be seen that the porosity of Examples 1 to 8 is significantly lower than that of Comparative Examples 3 to 4, and the conductivity of the composite solid electrolyte membrane of Examples 1 to 8 and the capacity retention rate after 500 cycles are significantly higher than those of Comparative Examples 1 to 4, indicating that compared with Comparative Examples 1-4, in Examples 1 to 8, by preparing the first solid electrolyte layer and combining the second solid electrolyte to undergo a phase change, the granular solid phase is transformed into a liquid phase with fluidity, so that the first solid electrolyte and the second solid electrolyte in the composite solid electrolyte membrane are more tightly bonded, and the second solid electrolyte can flow into the pores of the first solid electrolyte under a certain pressure after melting, thereby helping to fill the pores of the first solid electrolyte layer, effectively reducing the porosity of the composite solid electrolyte membrane, and the ionic conductivity of the prepared composite solid electrolyte membrane is improved, so that the capacity and cycle performance of the solid-state battery prepared by the composite solid electrolyte membrane are optimized.

[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0150] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The preparation method comprises: preparing a first solid electrolyte layer, wherein the first solid electrolyte layer comprises a first solid electrolyte; The first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing treatment, and cooled to obtain a composite solid electrolyte membrane; During the hot pressing process, the second solid electrolyte is transformed from a solid state to a liquid state.

2. The preparation method according to claim 1, characterized in that: The temperature T0 of the hot pressing treatment, the melting point T1 of the first solid electrolyte, and the melting point T2 of the second solid electrolyte satisfy: T0<T1; T0-T2=(0~50)℃; Preferably, the melting point of the second solid electrolyte is in the range of 80°C to 200°C.

3. The preparation method according to claim 1, characterized in that: Before the first solid electrolyte layer and the second solid electrolyte are subjected to hot pressing, the method further includes: laying a granular second solid electrolyte on the surface of the first solid electrolyte layer.

4. The preparation method according to claim 3, characterized in that: Laying m1g of granular second solid electrolyte on the surface of the first solid electrolyte layer, wherein the first solid electrolyte layer contains m0g of first solid electrolyte, m1 / m0=1:(3-50).

5. The preparation method according to claim 3, characterized in that: A granular second solid electrolyte is laid on the surface of the first solid electrolyte layer to form a solid electrolyte membrane precursor, and a sponge roller is used to roll the solid electrolyte membrane precursor.

6. The preparation method according to claim 1, characterized in that: The second solid electrolyte includes Li3MCl 6- x Br x , M is a trivalent metal element or a combination of metal elements with an average valence of trivalent, and x satisfies 0<x<6; Preferably, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ 、Bi 3+ , one or more of +3 valent lanthanide metals; Preferably, 2≤x≤5.

7. The preparation method according to claim 1, characterized in that: The step of subjecting the first solid electrolyte layer and the second solid electrolyte to hot pressing to obtain a composite solid electrolyte membrane comprises: After forming a second solid electrolyte on one side surface of the first solid electrolyte layer, a first hot pressing treatment and cooling are performed to form a first intermediate; After forming the second solid electrolyte on the surface of the first intermediate that does not contain the second solid electrolyte, the composite solid electrolyte membrane is formed by a second hot pressing treatment and cooling.

8. The preparation method according to claim 1, characterized in that: The hot pressing treatment satisfies at least one of the following conditions (1) to (3): (1) The hot pressing temperature of the hot pressing treatment is 80°C to 200°C; (2) The hot pressing time of the hot pressing treatment is 0.5min~30min; (3) The hot pressing pressure of the hot pressing treatment is 60MPa~600MPa.

9. A composite solid electrolyte membrane, characterized in that: It comprises a composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8.

10. A solid-state battery, characterized in that The invention comprises a positive electrode sheet, a negative electrode sheet and a composite solid electrolyte membrane according to claim 9 or a composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 8, located between the positive electrode sheet and the negative electrode sheet.

Citation Information

Cited By

  • All-solid-state sulfide negative-electrode-free lithium metal battery and assembling method thereof

    CN121439876A